Environmental Foreign Policy and Diplomacy in an Unequal World - Bimbo OGUNBANJO, PhD ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
This paper examines the intersections between various governmental tiers by concentrating on foreign policy and diplomatic players. It starts by outlining environmental foreign policy and the two primary methods used to characterize, evaluate, and clarify how it functions on many levels. This paper examines how the politics of foreign policy are evolving in light of the increasing complexity of the international system, after analyzing these two approaches. It highlights a number of foreign policy difficulties that arise when local and international concerns converge. Not unexpectedly, diplomacy is a major issue in international environmental politics and is also covered in this paper. It highlights how outcomes may be significantly influenced by the negotiating procedures that diplomats engage in, whether they are at official international conferences or private bilateral encounters. This present research provides an overview of the main themes covered in the field of environmental diplomacy, including game theory, leadership, domestic and international relations, issue linkage, non-state actors’ impact, norms and language, and negotiation and argumentation techniques. It makes the case that environmental diplomacy has lost credibility in recent years due to recurrent failures to draft a climate pact. The discussion of implications for future study on environmental foreign policy and diplomacy closes this work. It also emphasizes the necessity to reevaluate the function of diplomacy in government and the definition of the "outcome" of negotiations.